ANALISIS BUTIR SOAL BAHASA ARAB DI MTSN KOTA PAREPARE - Muhammad Atanda Musa; Rara Mutiah; Rahmani (IAIN Parepare, 2024)
This research aims to determine the quality of exam items based on qualitative analysis, focusing on aspects of content, construction, language, and the alignment of material with student capabilities. This study is qualitative research with a descriptive method. The primary data sources for this thesis research are the reviews from three informants, while the secondary data comes from related documents, including blueprints, questions, and answer keys for the final school exam in Arabic language subjects. The research instrument is a checklist filled out by the reviewers. The qualitative analysis in this research is tested using the panel technique, which examines exam items based on the rules of item writing, including reviews of the content, construction, and language/cultural aspects. The results of this study show that out of fifty exam items, five items did not meet the criteria in terms of content, eight items did not meet the criteria in terms of construction, four items were deficient in language aspects, and twelve items were inadequate in terms of alignment with student capabilities. Thus, out of fifty final school exam items, 24 items were considered good, and 26 items were considered poor. The implications of this study emphasize the need for improvements in the preparation of final school exam items to enhance the quality of evaluations and their alignment with student capabilities, as well as the importance of training for exam item writers to improve their competence in creating items that meet established standards